Indonesian University Students’ Perception and Expectation towards ICT Use in Learning English as a Foreign Language - Tubagus Zam Zam Al Arif (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2019)
This study aims to know the use of ICT frequency and purposes among EFL university students. It is also examines the students’ perception and expectation towards ICT use in learning English as a foreign language. This research applied quantitative approach with a survey research design. The data were collected from a survey which involved 337 students who were selected using stratified random sampling technique from 13 faculties of a state university in Jambi, Indonesia. The instrument used in collecting the data was a questioner adapted from Tri and Nguyen (2014). Data collected were analyzed by using SPSS 23 in form of descriptive quantitative. The findings indicated that the students spent more time in using ICT for general purposes than English learning purposes. On the other hand, they showed positive attitudes towards the use of ICT in learning English. The students perceive that ICT has the important role in improving their English language skills, and they expected that the teachers use ICT more frequently in teaching and learning process. Furthermore, they expected that campus can provide sufficient equipment and ICT access in each classroom in order to make the learning process become effective.